2012
DOI: 10.26719/2012.18.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics study on meglumine antimoniate sensitive and resistant Leishmania tropica isolated from Iranian anthroponotic cutaneous leishmaniasis patients

Abstract: In order to define the protein expressional changes related to the process of meglumine antimoniate resistance in anthroponotic cutaneous leishmaniasis (CL), we performed a comparative proteomics analysis on sensitive and resistant strains of Leishmania tropica isolated from Iranian CL patients. Cell proteins were analysed with 2-dimensional electrophoresis and differentially expressed proteins were identified by matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry. Image analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…Several techniques such as RT-PCR, microarrays, and proteomics are currently used to explore molecular markers of antimony resistance [14,15]. cDNA-amplified fragment length polymorphism (cDNA-AFLP) is one of the most sensitive technologies for detection of differentially expressed gene which does not require any prior information of gene sequences [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques such as RT-PCR, microarrays, and proteomics are currently used to explore molecular markers of antimony resistance [14,15]. cDNA-amplified fragment length polymorphism (cDNA-AFLP) is one of the most sensitive technologies for detection of differentially expressed gene which does not require any prior information of gene sequences [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the 2-DE method was applied for the detection of proteins that respond to drug resistance during leishmaniasis treatment [21]. The molecular weights of all detected proteins were 14.4 to 116 kDa which is close to Zarean and his colleagues study that they reported most of these proteins to have significant roles in transferring other proteins, heat shock proteins, skeletal proteins, and hypothetical proteins, specifically they have protective roles for DNA structure GMJ.2019;8:e1520 www.gmj.ir and normal metabolism in the cells [21,23,24]. Among the expressed proteins, specific proteins of each isolate may be secreted to patients' skin, which can be introduced as responsible protein/s for the clinical phenomenon of disease.…”
Section: Discussionmentioning
confidence: 99%
“…in 2012, proteomics technique was used to evaluate protein changes in resistant and sensitive isolates of L. tropica . The results determined an increase in the expression level of activated protein kinase C receptor (LACK) . Therefore according to the difference of the LACK protein expression in resistant and sensitive isolates, this gene was suggested to be one of the most probable factors involved in drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Following a proteomics study on L. tropica clinical isolates, which were sensitive and resistant to Glucantime treatment, a number of proteins with different expressions were identified by the mass spectrometry method . Among them, due to the importance of its physiological performance, the activated protein kinase C receptor (LACK) ( Leishmania analogue of the receptors of activated C kinase) antigen was selected, and its expression was investigated in RNA levels in L. tropica clinical isolates that were sensitive and resistant to Glucantime treatment.…”
Section: Introductionmentioning
confidence: 99%